The Future of IoT Applications in Port Management System in Malaysia - Shamsul Rizal, Syahirah; Hashim, Fazian (Research in Management of Technology and Business, 2025)
The Internet of Things (IoT) is the collective network of interconnected devices and the technology that enables communication between devices and the cloud. Nowadays, IoT has been adopted in port management system. The purpose of the study is to identify the issues, challenges, and trends of IoT applications in port management system, to study the key drivers of IoT applications in port management system, and to study the future image of IoT applications in port management system. The target respondents were selected among users of IoT applications in port management system in Westports Malaysia which is 359 respondents. The researcher utilized a quantitative method in this study. 359 questionnaires were distributed to the respondents via online survey and the survey return rate was 37.05%. This study employs foresight instruments such as STEEPV Analysis and SPSS analysis. STEEPV analysis is used to identify the issues, challenges, and trends of IoT applications in port management system. SPSS analysis has been used to show the result of the key drivers of IoT applications in port management system in the second phase of the research with impact-uncertainty analysis. 10 merged key drivers have been identified. The approach of impact-uncertainty analysis has been used to determine the future image of IoT applications in port management system. The top two drivers are technology reliability and IoT secure system in port management system. It indicates that these two drivers ensuring technology reliability and IoT security is crucial for future port management systems to maintain operational efficiency, safeguard data, and prevent disruptions in critical logistics networks. The scenario analysis has been formed based on the top two drivers and four scenarios will represent the possible outcome from 2024 to 2034. Hence, this research can help future researchers and developers increase their awareness of adopting IoT in the future.